Women's Leadership In Media: Gender Equality, Media Management And Content Policy - Abdullayeva Rahima Raimkul kizi (Academia Open, 2026)
General Background: Women’s leadership in the media is increasingly recognized as a key factor in advancing gender equality and democratic values within contemporary societies. Specific Background: Despite women’s substantial participation in journalism and the media workforce globally and in Uzbekistan, their representation in media leadership and decision-making positions remains limited, shaped by patriarchal structures, gender stereotypes, and the glass ceiling phenomenon. Knowledge Gap: There is insufficient integrated analysis linking women’s media leadership with content policy, media management practices, and gender representation in the Uzbek and Central Asian context. Aims: This study aims to analyze the role of women leaders in the media, their influence on media management and content policy, and their contribution to gender equality. Results: The findings indicate that women’s leadership is associated with more inclusive content, reduced gender stereotypes, and strengthened social justice narratives. Novelty: The study combines feminist media theory with regional empirical analysis to contextualize women’s media leadership in Uzbekistan. Implications: The results support policy, institutional, and educational strategies to expand women’s leadership and promote equitable media development.Keywords : Women's Leadership In Media, Gender Equality, Media Management, Feminist Media Theory, Glass CeilingHighlight : Women-led media organizations cover gender issues 40% more than others. Global female media leadership reached only 27% despite women comprising 40% of journalists. Glass ceiling barriers and patriarchal structures limit women's advancement to leadership roles.